Independent behavior and its relation to the creative abilities of students in Nazareth area - Kanaani, Mohamed Saleh Ahmed; Al - Ajili, Shatha (Journal of Educational and Psychological Sciences, 2017)
This study aimed to identify the independent behavior and its relation to the creative abilities of high school students in the Nazareth area in light of the variables of sex and grade. The study sample consisted of (236) male and female students from the tenth and twelfth grades of secondary school students in the Nazareth region in Palestine. They were chosen by random class method during the second semester of the academic year 2015/2016. To achieve the objectives of the study, the researcher developed the independent behavior scale developed by Roth, Assor, Kanat-Maymon & Kaplan, and the creative capacity scale developed in 2012 by Kaufman, and verified their reliability and consistency. The results showed that the level of independent behavior and creative abilities among secondary school students in the Nazareth area was within the intermediate level and that there was a statistically significant correlation between the level of independent behavior and the creative abilities of high school students. The results showed that there were statistically significant differences in the level of independent behavior among students due to the gender variable and for females. There were no statistically significant differences in the level of their independent behavior due to the variable of the school class. There were no statistically significant differences in the level of creative abilities of students due to gender and grade School. The study recommends that the development of independent behavior and creative abilities of high school students in the Nazareth region be considered higher than the average for the current study.
Keywords: behavior; independence; creative abilities; Nazareth